2017
DOI: 10.5098/hmt.9.3
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Radiative Flow of Nanofluid Past a Moving/Stationary Riga Plate

Abstract: The effect of non-linear thermal radiation on nanofluid flow over a riga plate is studied. Under some conditions, our problem reduces to the Blasius problem and Sakiadis problem. Similarity transformation is used to convert the governing steady Navier-Stokes equations into a system of coupled nonlinear differential equations, which are then solved numerically via Runge-Kutta-Fehlberg 45 order method along with a shooting method. Influence of parameters involved on velocity, temperature and concentration profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Oyelakin et al (2017) described that an unsteady MHD three-dimensional casson nanofluid flow over a porous linear stretching sheet with slip condition. Ramesh and Gireesha (2017) have been studied that a non-linear radiative flow of nanofluid past a moving/stationary riga plate. Stanford Shateyi (2017) has been stated that heat and mass transfer for natural convection MHD flow over a permeable moving vertical plate with convective boundary condition in the presence of viscous dissipation.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Oyelakin et al (2017) described that an unsteady MHD three-dimensional casson nanofluid flow over a porous linear stretching sheet with slip condition. Ramesh and Gireesha (2017) have been studied that a non-linear radiative flow of nanofluid past a moving/stationary riga plate. Stanford Shateyi (2017) has been stated that heat and mass transfer for natural convection MHD flow over a permeable moving vertical plate with convective boundary condition in the presence of viscous dissipation.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…The examinations of nanofluids were encompassing wide area of fluid dynamic studies. Accordingly, Ramesh and Gireesha have computed the impacts of nanofluid past a Riga plate with nonlinear radiative heat transfer. Moreover, the influences of energy generation of nanoliquid past a disk were studied by Mahanthesh et al They reckoned out that the Nusselt number is boosted with an addition of nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies 10–14 reveal the significance of heat transfer on Riga plate under various conditions. Ramesh and Gireesha 15 studied laminar electromagnetohydrodynamic (EMHD) nanofluid flow on a Riga plate considering nonlinear thermal radiation. Abbas et al 16 reported an observation on the presence of nanoparticle and gyrotactic microorganism in EMHD flow past a porous Riga surface.…”
Section: Introductionmentioning
confidence: 99%